Електронні джерела будівельної нормативної документації - Комова, Марія; Вовк, Наталія (Видавництво Львівської політехніки, 2012)
This article describes the main sources of information about state building codes and Researched online resource standards of Ukraine for construction companies. www.dbn.at.ua (DBNU)and the database: "Bud-Inform" and "Normative-Pro".